The Hearts of Men - Butler, Nickolas (New York, NY : Ecco, an imprint of HarperCollinsPublishers, 2017)
A scarred Vietnam veteran and successful businessman reflects on his teen years as a social outcast and friend to a popular youth during a summer camp reunion marked by selflessness and an unthinkable event involving his friends family members.
Keywords: Male friendship -- Fiction; Veterans -- Fiction; Boy Scouts -- Fiction; Camps -- Fiction; Fiction